PREGNANCY INTENTION AND UTILIZATION OF MATERNAL AND CHILD HEALTH CARE SERVICES IN INDONESIA - Ika Saptarini; Diahhadi Setyonaluri (Jurnal Kesehatan Reproduksi, 2018)
Background: Antenatal care, delivery by skilled birth attendants postnatal care and completed immunization help improve maternal and child health. Objective: This study investigates the association between pregnancy intention and utilization of mother and child health care. Method: The study used The Indonesian Demographic Health Survey 2012. Four regression models were used to identify the association between pregnancy intention and continuum of care for mothers and their children. Results: More than one-fifth (25.5%) of the respondents received the five types of maternal and child health care. Fifteen percent of women reported that their last pregnancy was undesirable. Pregnancy intention was significantly associated with receiving adequate antenatal care (OR: 0.53, 95% CI, 0.46-0.60), utilization of antenatal care and delivery by skilled birth attendants (OR: 0.62, 95% CI, 0.55-0.71), utilization of antenatal care, skilled birth attendance and postnatal care (OR: 0.82, 95% CI, 0.72-0.93), but not for utilization of antenatal care, skilled birth attendance, postnatal care and completed immunization (OR: 1.06, 95% CI, 0.91-1.22) after controlling for socio-demographic variables and obstetric factors. Conclusion: Interventions are needed to reduce unintended pregnancies such as improving access to family planning services.